2018
DOI: 10.1111/jonm.12619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical leadership, structural empowerment and psychological empowerment of registered nurses working in an emergency department

Abstract: The results show that for nurses to be able to provide clinical leadership to their patients and colleagues, management must create empowering environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 34 publications
6
69
1
1
Order By: Relevance
“…This structure ranked first in Greco et al's study (Greco et al, ) and Young‐Ritchie et al's study (Young‐Ritchie, Spence Laschinger, & Wong, ). The results showed that the nurses respected learning activities and professional and personal development, and had self‐dependence in nursing profession and regard it as an opportunity to enrich their lives (Connolly et al, ). When supervisors empower nurses to do their work in efficient ways (Greco et al, ) and do their best to comply with Maslow's hierarchy of needs, nurses are more probable to experience self‐actualization and self‐esteem (Ouyang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This structure ranked first in Greco et al's study (Greco et al, ) and Young‐Ritchie et al's study (Young‐Ritchie, Spence Laschinger, & Wong, ). The results showed that the nurses respected learning activities and professional and personal development, and had self‐dependence in nursing profession and regard it as an opportunity to enrich their lives (Connolly et al, ). When supervisors empower nurses to do their work in efficient ways (Greco et al, ) and do their best to comply with Maslow's hierarchy of needs, nurses are more probable to experience self‐actualization and self‐esteem (Ouyang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Oliver's et al study conducted on the clinical nurse managers (CNMs), access to formal power showed the lowest mean (Oliver et al, ). Studies, found that emergency nurses in New Zealand (Connolly et al, ) and nurses in a teaching hospital in Turkey feel they have low levels of formal power (Dirik & Intepeler, ). These findings indicate that nurses at every level, even in management, lacked autonomy and control over nursing work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations